Histone epigenetic modifications and their relationship with cancer: a comparative medicine view - Senhorello, Igor Luiz Salardani; Tinucci-Costa, Mirela [UNESP] (Univ Federal Santa Maria, 2023)
Epigenetic modifications have become highly important in the study of cancer pathogenesis due to research showing that changes in the expression of DNA-associated proteins can affect gene expression but may be reversible after treatment. The changing histones are being studied on a large scale in medicine while recent studies also show this relationship in veterinary medicine. Histone deacetylation is related to tumor progression and overexpression of histone deacetylases (HDACs) is responsible for these changes. The silencing of tumor suppressor genes related to epigenetic changes favors tumor progression; however, using HDAC inhibitors has been shown to effectively reverse these histone changes while having anticancer effects. This research provided an overview of comparative medicine between humans and dogs concerning epigenetic changes while showing the physiological mechanisms and the relationship between cancer and epigenetics, specifically regarding histone acetylation and deacetylation. This overview should contribute to a better understanding of epigenetics and cancer and their relationship with new target-molecular therapies in veterinary medicine and the importance of such studies.
Keywords: hypoacetylation; canine; deacetylation; tumor; treatment